Ruminations of Ipome - Usongo, Kenneth (Book collections on Project MUSE., 2014)
Breadth taking in range of subject explored and profound in depth of emotions evoked, this collection of poems chronicles different shades of emotions resulting from personal loss and love, as well as celebrates and critiques issues of culture, nature, place, people, ethics, and politics. The language is luminous and honed by refreshing and suggestive imagery.